Overcoming the coupled climate and biodiversity crises and their societal impacts - Pörtner, H. O.; Scholes, R. J.; Arneth, A.; Barnes, D. K.A.; Burrows, M. T.; Diamond, S. E.; Duarte, C. M.; Kießling, Wolfgang; Leadley, P.; Managi, S.; McElwee, P.; Midgley, G.; et al. (Science, 2023)
Earth's biodiversity and human societies face pollution, overconsumption of natural resources, urbanization, demographic shifts, social and economic inequalities, and habitat loss, many of which are exacerbated by climate change. Here, we review links among climate, biodiversity, and society and develop a roadmap toward sustainability. These include limiting warming to 1.5°C and effectively conserving and restoring functional ecosystems on 30 to 50% of land, freshwater, and ocean "scapes." We envision a mosaic of interconnected protected and shared spaces, including intensively used spaces, to strengthen self-sustaining biodiversity, the capacity of people and nature to adapt to and mitigate climate change, and nature's contributions to people. Fostering interlinked human, ecosystem, and planetary health for a livable future urgently requires bold implementation of transformative policy interventions through interconnected institutions, governance, and social systems from local to global levels.
CRIS-Team Scopus Importer:2023-04-28